New frontiers on open standards for geo-spatial science. Issue 2 (3rd April 2017) - Bermudez, Luis
Abstract: The process of sharing of data has become easier than ever with the advancement of cloud computing and software tools. However, big challenges remain such as efficient handling of big geospatial data, supporting and sharing of crowd sourced/citizen science data, integration with semantic heterogeneity, and inclusion of agile processes for continuous improvement of geospatial technology. This paper discusses the new frontiers regarding these challenges and the related work performed by the Open Geospatial Consortium, the world leading organization focused on developing open geospatial standards that "geo-enable" the Web, wireless, and location-based services and mainstream IT.